Chemotherapy-induced mucositis pursuant to different phase of chemotherapy in children with acute lymphoblastic leukemia at Hasan Sadikin Hospital Bandung - Pertiwi, Arlette Suzy Puspa (Padjadjaran Journal of Dentistry, 2008)
Acute Lymphoblastic Leukemia is the most common Leukemia seen in children. This disease has a manifestation in the oral mucosa, which is caused by either the disease itself or its treatment by chemotherapy, such as mucositis. Oral mucositis is one of a common, debilitating complication of cancer chemotherapy. Mucosal toxicity depends on Several factors; one of them is the duration of the therapy. The aim of this study is to evaluate chemotherapy-induced mucositis pursuant to a different phase of chemotherapy in children with Acute Lymphoblastic Leukemia. Twenty children diagnosed with Acute Lymphoblastic Leukemia who received induction, consolidation, and maintenance chemotherapy of Hasan Sadikin Hospital were included in this study. The criteria used for assessing mucositis was based on general mucositis scale from WHO. Data were collected and presented in the form of tables and percentages. The results showed that every child had developed mucositis during the course of chemotherapy in the induction and consolidation phase, except one child in the maintenance group did not the. at the induction phase 14,3% had developed mucositis at scale 2 and 86,7 at scale 3, consolidation phase 50% at scale 2 and 50% at scale 1, and in maintenance phase 14,3% in scale 28,6% in scale 1, and 57,1 in scale 2. Generally, it was concluded that mucositis develops in every phase of chemotherapy but the scale is slighter as the course of chemotherapy enters the advanced phases.